The four loves - Lewis, C. S. (Clive Staples), 1898-1963. (Boston : Mariner Books/Houghton Mifflin Harcourt, 2012)
Analyzes the feelings and problems involved in different types of human love, including familial affection, friendship, passion, and charity.
Likings and loves for the sub-human -- Affection -- Friendship -- Eros -- Charity
Keywords: Love; Love -- Religious aspects -- Christianity; Virtues -- Religious aspects -- Christianity; Christian ethics